AKTIVITAS HEPATOPROTEKTIF MADU TERHADAP HEPAR DAN PERUBAHAN BERAT BADAN MENCIT YANG DIINDUKSI ALKOHOL - Nur Aini Hidayah Khasanah; Fajar Husen (Ensiklopedia of Journal, 2026)
Alcohol exposure can cause liver damage through oxidative stress, fat accumulation, inflammation, and cell degeneration. Honey is known to contain antioxidants that have the potential to provide a protective effect against hepatic damage. This study aims to determine the protective effect of Tresnojoyo honey on body weight, liver-to-body weight ratio, and histopathological findings in the livers of mice (Mus musculus) induced with 70% alcohol. This experimental study used a completely randomized design (CRD) with 3 treatments and 8 replicates. The treatments were control, 70% alcohol (0.5 mL/day), and 70% alcohol with added honey (0.25 mL/day) for 10 days. The parameters observed included changes in body weight, liver weight to body weight ratio, and histological lesions (steatosis, hepatocyte degeneration, inflammation, and congestion). The results showed that all treatment groups experienced weight gain (p,0.05), with no significant difference in liver weight ratio. The control group showed normal histological findings. The 70% alcohol group showed heavy statocytes, hepatocyte degeneration, inflammation, and congestion. Administration of Tresnojoyo honey to the alcohol group reduced the degree of inflammation and cell degeneration, although it did not completely eliminate hepatic injury. It was concluded that Tresnojoyo honey has hepatoprotective potential due to alcohol exposure, by maintaining body weight and reducing histopathological changes in the liver.